Carbon Dioxide Embolism During Transanal Total Mesorectal Excision: Case Report and Literature Review - Zhu, Youzhuang; Wang, Weiwei; Liu, Dingsheng; Zhang, Hong; Chen, Lina; Li, Zhichao; Qin, Shangyuan; Kang, Yihan; Chai, Jun (Frontiers in Surgery, 2022)
The actual incidence of carbon dioxide embolism during transanal total mesorectal excision (taTME) is unknown, but the reported incidence in the existing literature is reassuring. However, the incidence of CO2 embolism, which can be life-threatening, is severely underestimated. By reviewing the available data on carbon dioxide embolism during taTME and synthesizing other reports on CO2 embolism in laparoscopic procedures, we provide the first comprehensive account of the etiology, pathophysiology, and recommend tools to monitor carbon dioxide embolism during taTME. Additionally, we provide guidance and recommendations on preventive and therapeutic measures to minimize the adverse consequences of this potentially severe complication, knowledge about which we hope will improve patients’ safety.